Why freeze-casting brings different phase composition of calcium phosphates? - Mařáková, Lucie; Roleček, Jakub; Salamon, David (Elsevier, 2021)
The impact of freeze-casting on the porosity, pore distribution, and phase composition was studied and compared with conventional shaping techniques. A bimodal pore size distribution was observed in freeze-cast + freeze-dried samples, in contrast to the unimodal one in freeze-cast + air-dried and conventionally prepared samples. The densification of freeze-cast + freeze-dried samples started at about 50 °C higher than their conventional counterparts (~870 °C vs. 920 °C). Diffusion seems to be a key parameter for the phase transformation of HAP into -TCP during sintering. The residual HAP content in the sintered samples was influenced by used freezing rate and varied from 4% to 30% (unimodal samples), and from 7% to 16% (bimodal samples). Although further experiments must be carried out, our results showed that the freeze-casting parameters affect the resulting porosity and phase composition regardless of whether the freeze-drying or air-drying was used afterward.

The impact of freeze-casting on the porosity, pore distribution, and phase composition was studied and compared with conventional shaping techniques. A bimodal pore size distribution was observed in freeze-cast + freeze-dried samples, in contrast to the unimodal one in freeze-cast + air-dried and conventionally prepared samples. The densification of freeze-cast + freeze-dried samples started at about 50 °C higher than their conventional counterparts (~870 °C vs. 920 °C). Diffusion seems to be a key parameter for the phase transformation of HAP into -TCP during sintering. The residual HAP content in the sintered samples was influenced by used freezing rate and varied from 4% to 30% (unimodal samples), and from 7% to 16% (bimodal samples). Although further experiments must be carried out, our results showed that the freeze-casting parameters affect the resulting porosity and phase composition regardless of whether the freeze-drying or air-drying was used afterward.
Why freeze-casting brings different phase composition of calcium phosphates?
Keywords: Ice-templating; Robocasting; Indirect 3D printing; Whitlockite; Hydroxyapatite; Ice-templating; Robocasting; Indirect 3D printing; Whitlockite; Hydroxyapatite